The distribution of storage and diversion dams in the western mountains of South Arabia during the Himyarite period - Charbonnier, Julien (Proceedings of the Seminar for Arabian Studies, 2011)
At the beginning of the Christian era, the appearance of retaining dams represented a turning point in the history of landscape in the mountains of South Arabia. They allowed the irrigation of the valley floors for a long period by providing water storage. In this paper, a preliminary study of the distribution of these barrages over the Yemeni Highlands is set out. They were not randomly distributed but clustered around some Himyarite sites around which the land was intensively cultivated. Usually several dams were built along valleys, and they were sometimes associated with monumental terrace walls and others hydraulic infrastructures. Inscriptions help to date some of these dams to the beginning of the first millennium AD, while the proximity of the pre-Islamic sites could help us to give a chronological attribution to other sites.